Novel Determinants of Antibiotic Resistance: Identification of Mutated Loci in Highly Methicillin-Resistant Subpopulations of Methicillin-Resistant Staphylococcus aureus - Janina Dordel (American Society for Microbiology, 2014)
ABSTRACT We identified mutated genes in highly resistant subpopulations of methicillin-resistant Staphylococcus aureus (MRSA) that are most likely responsible for the historic failure of the β-lactam family of antibiotics as therapeutic agents against these important pathogens. Such subpopulations are produced during growth of most clinical MRSA strains, including the four historically early MRSA isolates studied here. Chromosomal DNA was prepared from the highly resistant cells along with DNA from the majority of cells (poorly resistant cells) followed by full genome sequencing. In the highly resistant cells, mutations were identified in 3 intergenic sequences and 27 genes representing a wide range of functional categories. A common feature of these mutations appears to be their capacity to induce high-level β-lactam resistance and increased amounts of the resistance protein PBP2A in the bacteria. The observations fit a recently described model in which the ultimate controlling factor of the phenotypic expression of β-lactam resistance in MRSA is a RelA-mediated stringent response. IMPORTANCE It has been well established that the level of antibiotic resistance (i.e., minimum concentration of a β-lactam antibiotic needed to inhibit growth) of a methicillin-resistant Staphylococcus aureus (MRSA) strain depends on the transcription and translation of the resistance protein PBP2A. Here we describe mutated loci in an additional novel set of genetic determinants that appear to be essential for the unusually high resistance levels typical of subpopulations of staphylococci that are produced with unique low frequency in most MRSA clinical isolates. We propose that mutations in these determinants can trigger induction of the stringent stress response which was recently shown to cause increased transcription/translation of the resistance protein PBP2A in parallel with the increased level of resistance.